Cerebrovascular Reactivity is Increased with Acclimatization to 3, 454 M Altitude. Issue 8 (August 2015) - Flück, Daniela; Siebenmann, Christoph; Keiser, Stefanie; Cathomen, Adrian; Lundby, Carsten
Controversy exists regarding the effect of high-altitude exposure on cerebrovascular CO2 reactivity (CVR). Confounding factors in previous studies include the use of different experimental approaches, ascent profiles, duration and severity of exposure and plausibly environmental factors associated with altitude exposure. One aim of the present study was to determine CVR throughout acclimatization to high altitude when controlling for these. Middle cerebral artery mean velocity (MCAvmean ) CVR was assessed during hyperventilation (hypocapnia) and CO2 administration (hypercapnia) with background normoxia (sea level (SL)) and hypoxia (3, 454 m) in nine healthy volunteers (26 ± 4 years (mean ± s.d.)) at SL, and after 30 minutes (HA0), 3 (HA3) and 22 (HA22) days of high-altitude (3, 454 m) exposure. At altitude, ventilation was increased whereas MCAvmean was not altered. Hypercapnic CVR was decreased at HA0 (1.16% ± 0.16%/mm Hg, mean ± s.e.m.), whereas both hyper- and hypocapnic CVR were increased at HA3 (3.13% ± 0.18% and 2.96% ± 0.10%/mm Hg) and HA22 (3.32% ± 0.12% and 3.24% ± 0.14%/mm Hg) compared with SL (1.98% ± 0.22% and 2.38% ± 0.10%/mm Hg; P < 0.01) regardless of background oxygenation. Cerebrovascular conductance (MCAvmean /mean arterial pressure) CVR was determined to account for blood pressure changes and revealed an attenuated response. Collectively our results show that hypocapnic and hypercapnic CVR are both elevated with acclimatization to high altitude.